An in cellulo-activated multicolor cell labeling approach used to image dying cell clearance. Issue 15 (3rd July 2019) - Shi, Yilong; Zhu, Rui; Xue, Zhongwei; Han, Jiahuai; Han, Shoufa
Abstract : Dying cell clearance is critical for myriad biological processes such as tissue homeostasis. Abstract : Dying cell clearance is critical for myriad biological processes such as tissue homeostasis. We herein report an enzyme-activated fluorescence cell labeling approach and its use for multicolor imaging of dying cell clearance. Diacetylated 4-hydroxymandelic acid (DHA)-conjugated dyes give rise to reactive quinone methides upon deacetylation in live cells, which in turn covalently labels cellular proteins. With partner cells tagged with distinct fluorescence, apoptotic cell clearance by Raw 264.7 macrophages and epithelial HeLa cells was captured by confocal microscopy, showing the potential of DHA-based cell labeling for investigating cell–cell interactions.